The effect of urban–rural resident basic medical insurance on physical health of the rural older adult in China - Pu, Xiaohong; He, Sichang; Lin, Xi (Frontiers in Public Health, 2024)
Urban-Rural Resident Basic Medical Insurance (URRBMI) is an important system for effectively transferring disease risks to the rural elderly. As China experiences rapid aging, maintaining the physical health of the rural elderly is key to achieving the goal of healthy aging. The study explores the impact of URRBMI on physical health of the rural elderly in China using the Chinese Longitudinal Healthy Longevity Survey (CLHLS) data in 2018. Ordinary least square models were used to analyze the relationship between URRBMI and physical health of the rural elderly, and we used instrumental variable method to address the potential endogenous problem. We find that URRBMI greatly improves physical health of the rural elderly. The heterogeneity analysis indicates that URRBMI contributes more significantly to the rural elderly in eastern areas and the advanced rural elderly. The results also suggested that URRBMI improves physical health of the rural elderly through increasing life satisfaction and enhancing the timeliness of medical services. This study implies that we need to further improve the participation rate, increase the actual reimbursement ratio and increase financial subsidies for URRBMI in central and western areas, and further integrate the distribution of medical resources to promote physical health of the rural elderly.